Instilling Value-Significance in Land Ownership in the Northern Cape Province - Parker, Gail, Denise (My University, 2021)
The concept of value-significance in landownership has been viewed from only one dimension – the economic dimension. This study focused on the intrinsic dimension, sometimes theoretically called “place attachment” to determine how this component could be infused in land reform support and maintenance programmes directed towards beneficiaries of the land redistribution programme in the Northern Cape province of South Africa. The current state of post-land redistribution programme is characterized with a plethora of problems that lead to discouraged beneficiaries, unproductive land use and ultimate land degradation. This study sought to answer the question, “How to instill value-significance in land ownership to beneficiaries of the land redistribution programme in the Northern Cape Province”. An interpretivist phenomenological approach was selected as method of inquiry, purposively selecting ten study participants from different cohorts of the land redistribution programme between the period 1994 to 2018. Semi-structured interviews were conducted to obtain in-depth insights, to describe the lived experiences of participants. Aligned with ethical standards, interviews were conducted and recorded on an audio recording device, with the permission of participants. Recorded data was transcribed and analyzed using both thematic analysis benchmarked to the COSTA QDA Technique and the webQDA software. Findings of the study culminated into thematic expressions, namely: land redistribution programme needs to be underpinned by a structured maintenance programme; lives of beneficiaries are transformed; beneficiaries aspire full ownership of the land for productive use. The study concluded in a rigorous synthesis of these thematic expressions and culminated in development of the INSTIL Framework for instilling value-significance in land ownership. It is recommended that the framework for instilling value-significance in land ownership be implemented to enhance the success of the land redistribution programme in the Northern Cape province. Key words: Identity, Instil, Land ownership, Place attachment, Value-significance
Keywords: Identity; Instil; Land ownership; Place attachment; Value-significance